Case Report: Early-Onset Charcot-Marie-Tooth 2N With Reversible White Matter Lesions Repeatedly Mimicked Stroke or Encephalitis - Huang, Huasheng; Zhang, Yu; Yang, Mingxiu; Lian, Baorong; Guo, Rui; Cao, Liming (Frontiers in Pediatrics, 2022)
Introduction: Charcot–Marie–Tooth disease (CMT) is a rare group of peripheral neuropathies with high clinical and genetic heterogeneity. CMT type 2N (CMT 2N) is a rare subtype of CMT. The clinical presentation mimics that of other diseases, frequently leading to misdiagnoses. We present a case of CMT 2N with posterior reversible encephalopathy syndrome (PRES), which repeatedly mimicked stroke or encephalitis. Case Description: An 8-year-old boy was admitted to the hospital with slurred speech and limb weakness that had persisted for one day. The physical examination revealed lethargy, dysarthria, and a positive bilateral Babinski sign. Cerebrospinal fluid analysis showed no abnormalities. Brain magnetic resonance imaging (MRI) revealed symmetrical abnormal signal areas in the paraventricular white matter and corpus callosum. The patient was suspected of having viral encephalitis and recovered rapidly after treatment. He was hospitalized three years later for limb weakness, barylalia, and facial paralysis persisting for one day. MRI showed an abnormal signal in the bilateral corona radiata. He was suspected of having had a stroke or encephalitis. He completely recovered after treatment. After a second three-year span, he was admitted for another stroke-like episode. The physical examination revealed facial-lingual hemiparesis, mild atrophy of the left thenar muscle, decreased muscle strength in the extremities, and disappearance of the tendon reflex. MRI revealed more pronounced abnormal signals in the bilateral centrum semiovale and corpus callosum. Antibodies against autoimmune encephalitis were negative. A nerve conduction velocity study showed motor and sensory four-limb nerve demyelination with axonal damage, most notably at the distal end. His symptoms resolved after active treatment. A follow-up MRI showed the complete disappearance of the abnormal white matter signal. Whole exon sequencing showed a heterozygous mutation [c.2093C>T(p.Ser698Phe)] in the alanyl-tRNA synthetase 1 gene (AARS1). His mutation, clinical features, and electrophysiological testing led to a diagnosis of CMT 2N. Discussion: Early-onset CMT 2N with PRES can often mimic stroke or encephalopathy. Individuals affected may show an MRI which has a characteristic PRES feature. Careful family history assessment, physical examination, nerve conduction studies, MRIs, and genetic testing are essential for early diagnosis. Further studies are required to confirm these findings.